Antifungal activity of aqueous plant extracts and effects on morphological and germination of Fusarium fruit rot pathogens - Abd Murad, Nur Baiti; Mustafa, Muskhazli; Shaari, Khozirah; Mohd Zainudin, Nur Ain Izzati (Penerbit Universiti Kebangsaan Malaysia, 2021)
Fusarium fruit rot caused by Fusarium species pathogens can be considered a threat to economic loss. The use of synthetic antifungals to control the pathogens has failed to the development of resistance of pathogens. Previous studies reported that plant extracts may contain various bioactive constituents that are able to control pathogen growth. Hence, the aims of this study are to examine the inhibition activity of some plant fresh extracts on mycelial growth and morphological changes of Fusarium oxysporum, F. proliferatum, and F. solani, causal agents of Fusarium fruit rot. Aqueous extract of selected plants was evaluated for their inhibition activity against all the three Fusarium pathogens under in vitro condition using poisoned food bioassay. Averrhoa bilimbi fruit extract demonstrated a highly significant effect against mycelial growth of the pathogens with fungal inhibition percentage of 80.51% for F. oxysporum, 61.28% for F. proliferatum and 58.97% for F. solani. The results showed that the highest formation of 100% extract has lowered the conidia concentration and germination percentage of F. oxysporum (35.43%), F. proliferatum (47.61%), and F. solani (38.67%) compared to the control. Significant shriveled mycelia were observed via scanning electron microscope (SEM) on the pathogens treated with A. bilimbi extract, indicating morphological changes occurred in the cell membrane compared to the control in which the mycelia were in normal form. This innovation, which can be prepared and applied at home, has the potential as an eco-friendly and a benign approach to control fruit rot pathogen.